AKSI BERSIH DAN PENATAAN LINGKUNGAN MELALUI PROGRAM KKN MAHASISWA DI DESA GAMLAHA KECAMATAN KAO UTARA - Christin Fika, Elfira; Rahamani, Glen V; Sasingan, Riddik; Maran, Martha G (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
The purpose of this activity is to rebuild the habit of mutual assistance for environmental cleanliness and arrangement of Gamlaha Village. Problems faced by the community include the cleanliness and arrangement of village equipment signage, as well as the numbering of community houses, This activity was carried out for ± 2 months (29 January 2022 - 31 March 2022) in Gamlaha Village, North Kao. Sub-district. The method used was in the form of mutual cooperation activities and hygiene actions in order to build environmental cleanliness and village arrangement, involving 12 KKN students, 2 Field Supervisors along with the Government and the community of Gamlaha Village. The results of the activity evaluation show that all activities designed together with the community and KKN students at the location can meet the targeted achievements, so that this activity can be said to provide benefits to the Gamlaha Village community